Identity Economics in Emily Brontë’s Wuthering Heights: An Empathetic Inquiry into Psychoanalysis (SCHOLARS: Journal of Arts & Humanities, 2022)
This paper aims to connect the interlocking ideas of how social signifiers psychologically develop utility function, theorized by George A. Akerlof and Rachel E. Kranton, in characters like Heathcliff, the protagonist of nineteenth-century English fiction Wuthering Heights by Emily Brontë. Heathcliff's motivation is a desire born out of circumstantial consequences, for example, to be with Catherine in life or wealthy like Linton's family. This paper pinpoints how only material wealth fails to give a sense of belongingness in Heathcliff's life, which he aimed at achieving in the second half of his transformative journey. In addition, this paper attempts to reason for the absence of identity in Heathcliff’s decision-making process, which means a lack of empathy or belongingness in Heathcliff’s ambition. This research leads to a hypothesis that if Heathcliff had been brought up in an empathetic environment, the readers would not have perceived such degradation of mental health as abusive actions that he performs. Through a qualitative inductive method, this paper analyzes the aspect of identity economics that focuses on empathy. Thus, this paper gives insight into how material wealth without empathy only amplifies, particularly Heathcliff's violent nature, thereby leading the protagonist to an end where peace is a hallucination like Catherine’s ‘ghost.’